2023
DOI: 10.1108/ijbm-07-2022-0292
|View full text |Cite
|
Sign up to set email alerts
|

Omnichannel retailing with brand engagement, trust and loyalty in banking: the moderating role of personal innovativeness

Abstract: PurposeThe purpose of this study is to analyze the effects of integration quality, perceived fluency and assurance quality on brand engagement and trust, and their impacts on brand loyalty in the omnichannel banking setting. It further explores the critical role of personal innovativeness and demographic characteristics as moderating variables for the propositions in the research model.Design/methodology/approachAn online survey of 1,547 respondents was carried out with bank customers located in the three larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Hidayat and Idrus (2023) state that when customers perceive service engagement as being fair and supportive of their needs and expectations, trust in their bank is stimulated. As such, customers' future intent to remain in a relationship with their bank is strengthened (Tran Xuan et al, 2023). Consequently, Farooq and Moon (2020) and Kwong et al (2023) confirmed the mediating role of trust in a B2C environment in multiple settings.…”
Section: The Mediating Role Of Trustmentioning
confidence: 93%
“…Hidayat and Idrus (2023) state that when customers perceive service engagement as being fair and supportive of their needs and expectations, trust in their bank is stimulated. As such, customers' future intent to remain in a relationship with their bank is strengthened (Tran Xuan et al, 2023). Consequently, Farooq and Moon (2020) and Kwong et al (2023) confirmed the mediating role of trust in a B2C environment in multiple settings.…”
Section: The Mediating Role Of Trustmentioning
confidence: 93%
“…Aligning with digital touchpoints and transformation, Tran Xuan et al. (2023) conducted a study in the context of omnichannel banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to prior research, customer engagement is crucial to creating long-lasting relationships between businesses and their clients. Creating "deeper and more meaningful connections between businesses and their customers" is how customer engagement is defined (Tran Xuan et al, 2023). Previous studies have acknowledged the crucial part that consumer engagement plays in development.…”
Section: Customer Engagementmentioning
confidence: 99%